Identification of principal traits for ratooning ability associated with cane yield and juice quality in sugarcane genotypes from advanced varietal evaluation trials - Kandasamy, Elayaraja; Shanthi, R.M (Journal of Sugarcane Research, 2021)
Any new sugarcane variety should have both high yield and superior juice quality to ensure profitability for both farmers and sugar mills. Varieties with good ratooning ability (RA) give additional income to the farmers without replanting. In the national varietal development program, eight elite genotypes were evaluated in Randomized Block Design along with two standards during 2017-18 (as plant crop) and 2018-19 (as ratoon crop) at ICAR-Sugarcane Breeding Institute, Coimbatore. Eight Sugareane genotypes from advanced varietal Trial (AVT) were evaluated to study the relationship among yield, juice quality and its Component traits traits for their RA. PCA was carried out using eleven quantitative traits to identify the important traits contributing to high ratoonability in terms of cane yield and sugar yield. Three principal components with eigen value more than one explained 80.93 % of the total variation. Results on PCA indicated that single cane weight, juice sucrose %, CCS %, cane yield and sugar yield were strongly associated and dominant in explaining the existing variability among the genotypes. of the eght test genotypes evaluated Co 12009 and VSI 12121 were identified as excellent ratooners as they recorded high cane yield, such as sugar yield combining appreciable field stand in the ratoon crop. These genotypes have high RA for juice quality traits sucrose% and CCS%. These two genotypes with good flowering intensity could be used in hybridization as parents for identifying hybrid progenies with better retainability.